Informality and segmentation in the Mexican labor market - Carlo Alcaraz; Daniel Chiquiar; Alejandrina Salcedo (Banco de México, 2015)
In developing countries, some workers have formal jobs while others are occupied in informal positions. One view regarding this duality suggests that sectors are segmented, which means that a worker in the informal sector identical to another in the formal sector cannot get a formal position due to entry barriers. A second view states that workers self-select into informal jobs. Previous research suggests that these two situations may coexist in the same labor market. In this paper we identify the proportion of informal workers who are in each situation for the case of Mexico. Using a simple model of self-selection with entry barriers into the formal sector, we estimate that between 10 and 20 percent of informal workers would prefer to have a formal job. While this result provides evidence of the presence of some segmentation in the Mexican labor market, it suggests that an important proportion of workers in the informal sector self-select into it.
Keywords: J42; J46; 330; Informality; Segmentation; Mexico; Labor Market